VD_FINDINFO HC / 2025 / 529 vom 17. September 2025 - VD Tribunal cantonal (2025)
INTERDICTION D'ALIÉNER, MESURE PROVISIONNELLE, EXPERTISE, CRÉDIT HYPOTHÉCAIRE, REJET DE LA DEMANDE | 178 al. 1 CC, 183 CPC (CH), 311 al. 1 CPC (CH)